2017
DOI: 10.17559/tv-20161011143721
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and exercises for paretic upper limb of stroke survivors

Abstract: Preliminary communicationThe article presents the issues of biofeedback in virtual reality (VR). This VR module in ELISE robot gives a possible re-arrangement of the damaged motor cortex which can be activated with the mediation of mirror neurons or through the subject's motor imagery. This ELISE robot will help to accelerate the recovery from various kinds of neurological disorders, especially from the effects of stroke. Four physical/education games in virtual reality are described in more detail. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Our online control experiments showed that the average success rate of exoskeleton control task was 88.48%±5.84%, which was higher than that of virtual character arm movement tasks in VR scenes. The reason is that the MI command in the exoskeleton control task uses real task actions to improve patients' perception and motion mechanisms [40]. Patients can perform more concrete MI based on the obtained perception experience, which can improve the model recognition accuracy.…”
Section: Our Designed Offline Training Experiments (Mi Recognition An...mentioning
confidence: 99%
“…Our online control experiments showed that the average success rate of exoskeleton control task was 88.48%±5.84%, which was higher than that of virtual character arm movement tasks in VR scenes. The reason is that the MI command in the exoskeleton control task uses real task actions to improve patients' perception and motion mechanisms [40]. Patients can perform more concrete MI based on the obtained perception experience, which can improve the model recognition accuracy.…”
Section: Our Designed Offline Training Experiments (Mi Recognition An...mentioning
confidence: 99%
“…Additionally, there are more complicated and time-consuming approaches identified in this category, including developments of exoskeleton robotic devices that focus on specific parts of the hand. These are studies in which robotic gloves were developed to control the fingers [35,42,61,79,[150][151][152][153][154][155][156], and in which robotic arms were created to cover the surface from the shoulder to the wrist [4][5][6][7][8][9][10][11]48,49,110,139,[157][158][159][160][161]. Additionally, many research teams have focused on the development of a handle to obtain control of the arm force and movement [12,56,135,[162][163][164][165][166][167][168][169][170][171][172][173] or similar robotics [174][175][176]…”
Section: Hardware Developmentmentioning
confidence: 99%
“…Miao et al found that male students are more receptive to this technology than females [6]. Conversely, D. Li's study revealed some students' uncertainty about the utility of VR in PE [7].…”
Section: Introductionmentioning
confidence: 97%